Strategic Innovation in Accounting Ethics: How Religious Spirituality Shapes Competitive Advantage in Developed and Developing Countries - Nur Farizha; Mutmainnah; Ernawaty Usman; Jurana; Mustamin (Yayasan Cerdas Pedia Indonesia, 2025)
The global accounting profession is currently navigating a profound crisis of confidence, necessitating a shift from mere regulatory compliance to a holistic integration of ethical values within the strategic core of organizations. This study investigates the intersection of religious spirituality and accounting ethics, exploring how